Citizen report card as a social accountability tool towards customer satisfaction / Marni Ghazali and Haris Abd Wahab - Ghazali, Marni; Abd Wahab, Haris (Universiti Teknologi MARA, Shah Alam, 2017)
Making public services more accountable and responsive to the needs and expectations of citizens could improve public service delivery. Thus, this study aims to identify the level of customer satisfaction in relation to service received. Secondly is to identify the level of implementation of the citizen report cards used and lastly to examine the effect of citizen report cards used on customers’ satisfaction at one of the Malaysian government agency. The target population is service users. Data was collected through a structured questionnaire to 400 service users specifically at one of the government agency in Selangor. The main analysis involved descriptive and inferential statistics in order to achieve the research objectives of the study. The findings from the study revealed that the level of customer satisfaction in relation to service received is at moderately high, while the level of implementation of the citizen report cards used is also at moderately high. Results also confirmed that the use of citizen report cards was significantly related to customer satisfaction, produces positive but very weak relationship with customer satisfaction. Therefore, the study findings provide significant insights especially to government agency to devote on continuous improvement and development with regards to the use of citizen report cards and its impact on customers’ satisfaction in relation to public service delivery.